Analisis Manajemen Strategi Berdasarkan Swot Untuk Peningkatan Daya Saing Dan Kualitas Mutu Pelayanan Rumah Sakit (Studi Kasus Di Rumah Sakit Punten Batu): Strategic Management Analysis Based on SWOT to Improve Competitiveness and Quality of Hospital Services: Case Study at Punten Batu Hospital - Dewi Septinasari Hasyim; Mela Lavenia (Jurnal Bisnis dan Ekonomi, 2026)
Abstract : Improving the quality of healthcare services is a crucial aspect in strengthening competitiveness in the healthcare sector. To enhance quality and competitiveness, Punten Batu Hospital implemented a SWOT analysis to analyze internal weaknesses and anticipated external challenges, as well as to identify strengths across both internal and external factors.   Objective : The aim of this study is to analyze the internal and external conditions of Punten Batu Hospital as a basis for developing strategies to improve the competitiveness and quality of hospital services.   Methods : This research uses a descriptive approach with qualitative methods. Data processing techniques include a SWOT analysis.   Research results : The results of the study indicate that improving competitiveness and service quality at Punten Batu Hospital can be achieved through the implementation of strategies formulated based on the results of a SWOT analysis. Based on the analysis, Punten Batu Hospital is in a fairly advantageous position because it has strengths and opportunities that can be maximized to develop organizational potential and utilize available opportunities.